DEVELOPMENT OF NATIONAL ARMY HAND-TO-HAND COMBAT AS A SPORT - Irkhin, V.N.; Gomzyakova, I.P.; Oldenburger, R.F.; Komarova, I.G. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the stages of development of army hand-to-hand combat as a sport in Russia. Methods and structure of the study. The scientific work used the analysis and generalization of scientific literature, statistical data, the practice of organizing army hand-to-hand combat (AHHC); specific methods of the history of pedagogy: historiographic, determinant-genetic and problem-genetic analyzes of the problem. Results and conclusions. Historical analysis has shown that the process of formation and development of sports army hand-to-hand combat is associated with socio-political and economic transformations in the USSR and Russia. During the development of periodization, the influence of the significance of historical, cultural, socio-political and economic factors in the development of our society and state, the idea of the gradual formation of individual elements of the AHHC was taken into account. Relying on the criterion "essential characteristics of army hand-to-hand combat as a unique system of martial arts" made it possible to identify the following stages of its development in our country: 1) 20s-70s XX century - the prerequisites for the emergence and the period of "hidden" development of the AHHC in line with the various types of existence of hand-to-hand combat in our country, primarily sambo; 2) 1979 -1995 - the period of emergence (the first championship of the airborne troops in the AHHC) and the formation of army hand-to-hand combat; the development of army hand-to-hand combat as a military-applied sport, its cultivation only in army units; 3) 1995 - 2016 - the progressive development of army hand-to-hand combat in Russia; cultivation of AHHC not only in army units, but also in police units, as well as in sports organizations; 4) 2016 - until now - the controversial nature of the development of army hand-to-hand combat in Russia: on the one hand, the increasing importance of the AHHC as a means of patriotic education of the younger generation, improving this sport (athletes' equipment, tactics, increasing the speed and dynamics of combat, increasing entertainment of duels, quantitative development of competitions, etc.) AHHC; and on the other hand, an increase in the competition of the AHHC from other types of martial arts; reduction in the number of children involved in AHHC.